x2 + 4x + 6 can not be factored.
If you want, you can reduce it to an expression with a single x term by comleting the square:
x2 + 4x + 6
= x2 + 4x + 4 + 2
= (x + 2)2 + 2
(x+4) (x+6)
x2 + 4x - 60 factors into (x + 10)(x - 6). You can use the FOIL method to check your answers when you factor.
6
x2+4x-12 = (x-2)(x+6) when factored
x2 + x - 6 = (x + 3)(x - 2)
(x+4) (x+6)
(6 - x)(2 + x)
x2 + 4x - 60 factors into (x + 10)(x - 6). You can use the FOIL method to check your answers when you factor.
6
x3 + 6x2 - 4x - 24 = (x + 6)(x2 - 4) = (x + 6)(x + 2)(x - 2)
x2 + 7x + 6 = (x + 6) (x + 1)
x2 + x + 6
(x + 6)(x - 2)
That does not factor neatly.
6
x2+4x-12 = (x-2)(x+6) when factored
x2 + x - 6 = (x + 3)(x - 2)